PENERAPAN MODEL PEMBELAJARAN INSIDE OUTSIDE CYRCLE (IOC) UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI PADA PESERTA DIDIK KELAS X - Arga, Kharisma Idola (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
Abstract: Problems in this study are 1) economic learning outcomes are still low, 2) learning activities of students that are still relatively low, 3) the learning process that occurs tends to still transfer information from teachers to students, not from the students themselves. and 4) competition in learning is still dominated by active and smart students only. In this study the authors used the learning model inside outside circle (IOC) with the aim of increasing the activity and economic learning outcomes of class X students in economic subjects at Natar 1 High School in 2019/2020 school year. This research is a Classroom Action Research (CAR). The subjects in this study were students of class X. IPS 2 SMA Negeri 1 Natar, amounting to 38 students. The research instrument used was a multiple choice test consisting of 20 questions, if correct it got a score of 5 and if wrong 0, while the observation sheet consisted of 6 aspects of observation with an observation score consisting of 1-4. Mastery learning outcomes in this study reached 80% of the total number of students. The results showed that the average score of student learning outcomes of 5.97. Mastery learning students also experienced an increase where in the first cycle of 63.89% and 86.11% in the second cycle, which obtained an increase in mastery learning from cycle I to cycle II of 22.22%. So it can be concluded that learning activities by applying the learning model inside outside circle (IOC) can increase the economic activity and learning outcomes of students in class X. IPS 2 SMA Negeri 1 Natar in the academic year 2019/2020. Keyword: Inside Outside Cyrcle (IOC) Learning Model, Learning Outcomes